The Effect of Academic Model Supervision on the Workload and Stress of Nurses in Hospitals: A Literature Review - Helvitia Bulu, Sandra; Vidya Trias Novita, Regina (Al Makki Health Informatics Journal, 2024)
Nurses often face high workloads and significant levels of stress due to the demands of complex work and high pressure. The academic supervision model is important because it can help nurses manage workload, improve skills and knowledge, and reduce stress levels. Effective supervision is expected to improve the quality of health services, job satisfaction, and have a positive impact on patients and the health system as a whole. This study aims to determine the influence of academic model supervision on the workload and stress of nurses in hospitals. This study uses a literature review method from research articles in the Scopus and Google Scholar databases published in 2014-2023 with the keywords "Supervision", "Academic Model", "Nurse Workload", and "Nurse Stress". Based on the analysis of 22 research articles, it was found that the supervision of the academic model had a positive impact on nurse performance, job satisfaction, work motivation, quality of nursing care, reduction of stress levels, and improvement of overall health service quality. Academic model supervision can help nurses improve skills and knowledge, improve services provided, develop professionalism, increase independence, improve nursing care, reduce workload, improve nurse performance, provide good emotional support, and continuous learning, and reduce the level of stress experienced by nurses. The implications of this research suggest that implementing academic model supervision in hospitals can lead to better nurse outcomes, including enhanced job satisfaction, reduced stress, and improved quality of care. Consequently, this can result in higher patient satisfaction and a more efficient and effective health care system overall.